ASSESSING THE TEMPORAL AND SPATIAL DISTRIBUTION OF DENGUE FEVER IN TEHSIL ADENZAI, DISTRICT DIR LOWER (The Research of Medical Science Review, 2024)
Tehsil Adenzai, District Dir Lower, and with the rate of prevalence also varying. This work here reports the highest prevalence at Chakdara at 58.95% which puts it at the top of the urgent list for increased testing and awareness campaigns. Ouch shares a similar rate at a prevalence of 43.02%, while moderate spread reports at Badwan and Gul Abad at 26.36%. Lower rates are found in Kharkani, Shiwa, and Asbnar, reflecting control measures are effective, or exposure is at the minimum. Gender-wise, Chakdara is predominant in females and in males for Ouch. Many of the children belong to the age group 0-15 years. This anomaly in the 46-60 age group calls for occupational or environmental factors. DHQ Chakdara has a prevalence rate of 72.2 percent since it is a referral hospital. Summarily, through locally tailored interventions among gender and age groups, sustaining surveillance, and engaging communities, this region would be made to control dengue.